Effect of Waste Facilities on Community Compliance in Benteng Medan - Nuri Jannaturrahmi Tambusai; Franklin Asido Rossevelt; Dara Aisyah; Nayla Rahmadia Sarif; Tasya Pratiwi; Jessica Patricia Br Manik (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyze the effect of the availability of waste facilities on community compliance in disposing of waste at Benteng Field, Medan. The method used is a quantitative method with data collection techniques through questionnaires. The data were analyzed using descriptive statistics, validity and reliability tests, Pearson correlation tests, and simple linear regression. The results showed that the availability of trash facilities had a positive and significant effect on the level of public compliance in disposing of trash in its proper place at Benteng Field, Medan, with a p-value < 0.05. These findings indicate that adequate facilities in terms of number, condition, and placement were proven to encourage visitors to be more disciplined in maintaining the cleanliness of public areas. This study provides empirical evidence to reinforce the importance of providing adequate sanitation facilities as an environmental management strategy, particularly in urban public spaces.